Parotitis with secondary syphilis: a case report. - Hira, S K (1984)
Painless swelling of the parotid salivary gland was observed in a patient presenting with secondary syphilis. This case is of special interest to venereologists and surgeons as parotitis associated with syphilis may be mistaken for common tumours of the parotid glands. A diagnosis of syphilitic parotitis should be considered in patients presenting with swollen parotid salivary glands in countries where syphilis is prevalent.